'Does peacekeeping deter terrorism?'. Issue 1 (2nd January 2021) - Kruglova, Anna
ABSTRACT: This article examines the effect of the presence of UN peacekeeping forces on the scale of domestic terrorist violence in civil war-torn countries. By employing matching and regression analysis, I explore two samples: one contains information about countries during the active phase of fighting (in-war); and the other relates to after the fighting has finished. I find that the presence of UN peacekeepers during the active phase of fighting has no significant effect on the number of terrorist attacks, but it decreases the number of terrorist attacks after the war is over.